The Impact of Saltwater Intrusion on Rice Cultivation and Aquaculture in Ham Tan commune, Tra Cu District, Tra Vinh Province, Mekong Delta, Vietnam - Le Thi Hoa (European Scientific Journal, ESJ, 2023)
This article discusses the impact of saltwater intrusion on rice cultivation and aquaculture in Ham Tan commune, Tra Cu District, Tra Vinh Province, Mekong Delta, Vietnam. Based on in-depth interviews and sociological surveys conducted in Ham Tan commune, Tra Cu District, Tra Vinh Province, the article highlights the main findings. Firstly, rice cultivation and aquaculture in Ham Tan are multidimensionally affected by the negative impacts of saltwater intrusion. Secondly, saltwater intrusion reduces crop yields and decreases the area available for rice cultivation. It also increases labor days and investment costs in rice production. Thirdly, saltwater intrusion decreases the productivity of aquaculture. In fact, a significant number of households engaged in aquaculture experienced complete losses due to saltwater intrusion.